Performance evaluation of various solar photovoltaic module technologies under tropical climate conditions at Melaka, Malaysia - Gan, Chin Kim; Jabawi, Hayder Salah Mohammed; Baharin, Kyairul Azmi (Medwell Journals, 2019)
The system performance of a grid-connected solar photovoltaic system is one of the most important parameters to monitor the health of the system. This study aims to evaluate the performance of three (3) PV module technologies, namely Thin-Film (TF), Heterojunction with Intrinsic Thin layer (HIT) and monocrystalline which are installed at Universiti Teknikal Malaysia Melaka (UTeM) under Malaysia tropical climate conditions. Actual annual solar resources and PV system’s energy output were recorded for two (2) consecutive years, i.e., 2014-2015 using the weather station and solar monitoring system installed in the laboratory. The annual average final yield of the PV systems ranged from 1452-1579.5 kWh/kWp/year. The average annual performance ratio of the 3 PV systems ranged from 80-91.4% while the average annual capacity factor of the 3 PV systems ranged from 16.5-18%. The average annual system losses of the 3 PV systems ranged from 154.46-302.15 kWh/kWp while the average annual array capture losses of the 3 PV systems ranged from -6.36-59.71 kWh/kWp. Outdoor assessment shows that the thin-film PV system had the highest performance ratio and capacity factor. Furthermore, the thin-film PV system produced the lowest system losses and array capture losses, compared to HIT and monocrystalline PV systems